2010
DOI: 10.1115/1.4000940
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Wear on the Performance of Multirecess Hydrostatic Journal Bearing Operating With Micropolar Lubricant

Abstract: The objective of the present work is to study theoretically the influence of wear on the performance of four-pocket capillary-compensated hydrostatic journal bearing operating with micropolar lubricant. In the present study, the lubricant containing additives and contaminants is modeled as micropolar fluid. The modified Reynolds equation for micropolar lubricant is solved using finite element method along with capillary restrictor flow equation as a constraint together with appropriate boundary conditions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…Geometric and operating parameters for conical journal bearing system. [7][8][9][13][14][15][16][17][18]20,19 Bearing aspect ratio (λ) 1 Figure 3. Variation of maximum fluid-film pressure (p max ) versus radial load W r À Á .…”
Section: (A) Radial Load Capacity ( ) Vs Radial Eccentricity Ratio (mentioning
confidence: 99%
See 2 more Smart Citations
“…Geometric and operating parameters for conical journal bearing system. [7][8][9][13][14][15][16][17][18]20,19 Bearing aspect ratio (λ) 1 Figure 3. Variation of maximum fluid-film pressure (p max ) versus radial load W r À Á .…”
Section: (A) Radial Load Capacity ( ) Vs Radial Eccentricity Ratio (mentioning
confidence: 99%
“…In recent years, many investigators [13][14][15][16][17] studied the effect of micropolar lubrication on the performance of different types of fluid-film bearings such as hydrodynamic journal bearing, step bearing and lobbed hydrodynamic bearing. The studies 18,19 dealt with the influence of micropolar lubrication on the performance of hydrostatic and hybrid journal bearing. The studies [13][14][15][16][17][18]20,19 indicate that the use of micropolar lubricant results in a significant enhancement in the performance of the bearing system vis-à-vis Newtonian lubricant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicodemus et al [21] studied the influence of wear on the performance of capillary compensated four pocket hydrostatic journal bearing operating with micropolar lubricant for two different loading arrangements. The study revealed the influence of wear on bearing static performance characteristics, which is significantly higher for a bearing lubricated with micropolar as compared to bearing lubricated with Newtonian lubricant.…”
Section: Introductionmentioning
confidence: 99%
“…De Pellegrin, Dennis V.and Hargreaves, Douglas J. pointed out that it is that the bearing with constant external turbocharged prolonged the service life of the bearing and decreased the friction and wear ,and simulated the influence the size and shape of the groove have on the bearing performance [3]. Nicodemus, E. Rajasekharand Sharma, Satish C. studied the theoretical influence micro polar lubricants have on wear properties of hydrostatic bearing with 4-vessel and compensation of capillary resistor, simplified the lubricants with additive into micro polar fluid, and solved the flow equation and the Reynolds equation using the finite element method [4]. In 2001, M. Wen-qi, J. ji-hai, Z. Ke-ding, has numerically analyzed the characteristics of fluid flow in annular hydrostatic bearing considering variable viscosity and different working condition by the finite element method, obtained viscosity field distribution , and compared with in constant viscosity.…”
Section: Introductionmentioning
confidence: 99%